Strategi Pengenalan Produk UMKM Toko Aqilla Di Desa Sidowayah Melalui Media Promosi Offline Dan Online - Zulfa Al Aqsha An Najwa; Muhammad Aziz Syaifuddin; Riyan Andi Prasetyo; Hetty Muniroh (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This Community Business Work Program (KKU) was conducted at Warung Aqilla, a micro, small, and medium enterprise (MSME) specializing in light snacks such as iced beverages, sausages, and seblak. Initial observations identified several key problems, including the absence of promotional media, lack of a business banner, and difficulty for new customers in locating the business. To address these issues, the KKU team from Universitas YPPI Rembang implemented three main programs: the creation of a business banner, a digital location map, and a TikTok social media account. These programs aimed to improve visibility, expand promotional reach, and assist the business owner in managing and growing the enterprise. The results of this program showed that the owner felt significantly helped by the newly created promotional media, which succeeded in attracting new customers and enhancing the business’s local presence. This KKU activity is expected to provide long-term benefits for the development of Warung Aqilla as an MSME.